Inovasi dalam Manajemen Perubahan Pendidikan di Pondok Pesantren Al-Hikmah Purwoasri Kediri - Ahmad, Ahmad (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
The changing times and the demands of modernity require Islamic educational institutions to adapt without abandoning the traditional Islamic values as their main identity. This study aims to analyze change management in educational development in response to these challenges. This study uses a qualitative case study design. Data were collected through in-depth interviews, participant observation, and document analysis using Kurt Lewin's change management theory framework, which includes the stages of unfreezing, changing, and refreezing. The results show that change management in pesantren is carried out through three main stages: planning based on needs analysis and strengthening the religious curriculum, implementation through the integration of formal and traditional education, improving the competence of teaching staff, and evaluation oriented towards continuous improvement and strengthening the pesantren culture. A key finding of this study is the concept of Change Renaissance Pesantren, namely, adaptive, non-radical change, in which the institutional shift from state to private ownership does not alter the pesantren's basic values. In conclusion, change management based on active participation can make pesantren a model of Islamic education that is adaptive, character-based, and relevant to the demands of the times.